ANALISIS KETERKAITAN PENGAKUAN PENDAPATAN DAN LABA PADA PERUSAHAAN KONSTRUKSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Iswadi, Iswadi; Khirnika, Khirnika (Jurnal Akuntansi dan Keuangan, 2017)
This study aimed to determine the effect of operating income recognition on the income statement. The data used were secondary data in form of the income statements of construction companies listed on the Indonesia Stock Exchange (IDX) from 2013 to 2016. The objects in this study were selected based on the highest profit value and were taken 3 companies as the sample. This study uses descriptive analysis as data analysis. The results showed that the three companies, namely PT Pembangunan Perumahan, PT Surya Semesta Internusa Tbk, and PT Waskita Karya Tbk, measured their income by using the percentage settlement method and each had a different level of income each year and were in accordance with the applicable accounting standars namely Standard Statement Financial Accounting (PSAK No. 34).